Direct Applicability of Generally Accepted Principles of International Law in Legal Order of the Republic of Slovenia - Anton Olaj (Central European Public Administration Review)
Self-executing, incorporated and generally accepted principles of international law have been used directly in legal order of the Republic of Slovenia. Systematic records of these identified and enforced norms do not exist. It is difficult for lawyers and judges to get acquainted with them. The predicament is even greater because, with the exception of the Court of Justice of the European Union, a translation of the relevant case law of international tribunals is not available. Generally accepted principles of international law are applicable in Slovenian legal order per se. Despite that, it is not entirely clear how administrative bodies should react in situations where the rights and obligations of legal entities are on the one hand regulated by law and customary international law but on the other hand are contradictory.